Essentials of pediatric nutrition - King, Kathy , 1969-; Samour, Patricia Queen (Jones & Bartlett Learning, 2013)
Abridged version of: Pediatric nutrition / edited by Patricia Queen Samour, Kathy King. 4th ed. c2012